2008
DOI: 10.1590/s1516-89132008000100020
|View full text |Cite
|
Sign up to set email alerts
|

Variation in phytate accumulation in common bean (Phaseolus vulgaris L.) fruit explants

Abstract: The in vitro synthesis of phytate was studied in common bean fruit explants. Different concentrations of sucrose; phosphorus (P); myo-inositol; abscisic acid (ABA); glutamine and methionine, were tested. Fixed concentrations of these compounds were tested at different periods (0, 3, 6 and 9 days

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The absorbance of the salicylate-Fe (III) complex was determined on a spectrophotometer (BioTek Instruments, Inc., USA, 500 nm). The PA concentration was calculated using a standard curve (0–60 mg/mL) that was obtained with phytic acid dipotassium salt (Sigma-Aldrich, Canada) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The absorbance of the salicylate-Fe (III) complex was determined on a spectrophotometer (BioTek Instruments, Inc., USA, 500 nm). The PA concentration was calculated using a standard curve (0–60 mg/mL) that was obtained with phytic acid dipotassium salt (Sigma-Aldrich, Canada) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, this compound may exert antioxidant activity by complexing with iron, reducing the formation of free radicals and peroxidation of membranes, which could provide anticarcinogenic power (Thomson & Zhang, 1991). Therefore, there is an increased interest in the manipulation of phytate in grains worldwide, either to increase or decrease their concentration in foods (Coelho, Bellato, Garcia, Vitorello, & Azevedo, 2008;Coelho, Benedito, Figueira, Vitorello, & Azevedo, 2007;Coelho, Tsai, & Vitorello, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, taking the first day of germination as control, on the 4 th day, the PA content decreased to 70.42 and 75.26% in BRS191 and C11, respectively, which was in agreement with Agostini and Ida (2006a) who observed the germination of hybrid sunflower M734, and previously reported by Egli et al (2002) who investigated the germination of several grains and seeds. On the other hand, Coelho et al (2008), from in vitro synthesis of phytate in culturing bean fruit explants concluded that different concentrations of phosphorus, sucrose, abscisic acid, glutamine and methionine caused an increase in the phytate of bean seed, showing that it could be possible to alter its content. Phytases activities in non-germinated seeds varied from 0.08 UI/g for both BRS191 and C11, which demonstrated the correlation between the PA content and both enzyme activities.…”
Section: Pa and Enzyme Activity In Germinationmentioning
confidence: 99%
“…Agostini and Ida (2006a) investigated the germination of hybrid sunflower M734 by response surface methodology and observed minimal phytate and acid phosphatase activity on the 6 th day of germination at 30° C. The best conditions for phytase activity were the 4 th day of germination at the same temperature. Other studies by different techniques suggest a decrease or control in PA content (Reddy et al, 1982;Coelho et al, 2008). Phytases or mio-inositolhexaphosphate phosphohydrases (EC 3.1.3.26) or 6-phytases are phytate-specific phosphatases that hydrolyze PA or mio-inositol hexaphosphate to inositols and phosphates (Reddy et al, 1982).…”
Section: Introductionmentioning
confidence: 99%